Seasonal variations in the body composition of lightweight rowers - Morris, F. L.; Payne, W. R. (British Journal of Sports Medicine, 1996)
OBJECTIVE: To monitor the seasonal body composition alterations in 18 lightweight rowers (six females, 12 males) across a rowing season incorporating preseason, early competition, competition, and postseason. METHODS: Subject age was 23.1 (SD 4.5) years, height 170.8 (5.6) cm (female, 23.5 (3.5) years, 180.5 (2.7) cm (male). Body weight, fat mass, and fat-free mass (FFM) were assessed using dual energy x ray absorptiometry (DXA-L Lunar) and skinfold techniques. Weight control techniques were documented before major regattas by a questionnaire. RESULTS: Female body weight was reduced from 61.3 (2.9) to 57.0 (1.1) kg (5.9%), while male body weight was reduced from 75.6 (3.1) to 69.8 (1.6) kg (7.8%) preseason to competition season respectively. These body weight reductions were mirrored by a significant reduction in fat mass as indicated by the sum of skinfolds [female seven sites: 80.9 (8.1) to 68.2 (11.8) mm; male eight sites: 54.2 (8.7) to 41.8 (4.8) mm], percentage body fat [female 22.1 (1.0) to 19.7 (2.4)%; male 10.0 (0.9) to 7.8 (0.8)%], and total fat [female 12.5 (5.2) to 10.9 (1.4) kg; male 7.3 (1.9) to 5.6 (1.8) kg] (DXA). In contrast, no changes were observed in FFM despite a season of intensive rowing training. Seasonal body weight control was achieved through reduced total energy and dietary fat intakes. Acute body weight reductions were achieved by exercise in 73.3% of participants, food restriction in 71.4%, and fluid restrictions in 62.9%. CONCLUSIONS: Seasonal body weight alterations in lightweight rowers are in response to a significant reduction in fat mass. However, the weight restrictions appear to be limiting an increase in FFM which could be beneficial to rowing performance.